IMPORTANT FACTORS AFFECTING MODERN CLOUD TECHNOLOGIES USING IN EDUCATION - Mamanazarovich, Kurbanov Zafar; Hamdamovich, Ayupov Ravshan (The journal of contemporary issues in business and government, 2021)
Cloud solutions are promising directions among modern technologies using in education. Many companies today are gradually moving their business processes including education business to the cloud or preparing to move to it. Cloud technology was one of the ideas that first emerged in the end of 1980s when scientists were talking about the concept of distance education. One of the main reasons for implementing this concept was the high cost of computers and software in the case of using systems without using of cloud technologies in distance education. Therefore, the idea of connecting several employees to a common cloud processor at the same time was considered. Implementation of cloud computer technologies began in 1990s, and the first economically successful solution was released around 2000s. In the case of using cloud computer capabilities customers could purchase the software power needed to perform the calculations. The second major factor influencing today’s clouds is the ability to connect to a global network for everyone in everywhere. The basic principle of this technology is that users can access services from anywhere in the world.